Internal Antecedents of Management Innovation - Mie Harder (Copenhagen Business School (CBS), 2011)
This dissertation explores the internal antecedents of the phenomenon labeled management innovation. Management innovation refers to the implementation of new management practices, processes, techniques or structures that alter the way the work of management is performed. In other words, management innovation refers to changes in what managers do and how they do it.
hdl:10398/8295
Keywords: 650